The Study of Pyrolysis Temperature Toward Total Phenol Content, Total Acid Content, and Ph in Spent Coffee Ground Liquid Smoke - Kwee Amanda Gracia; Yunita Ismail (Jurnal Serambi Engineering, 2022)
The trend of spending time in coffee shop increases the spent coffee ground (SCG). Most of the SCG goes to landfills because it does not have a selling value. One of the ways to utilize SCG is utilize it as a biomass for liquid smoke (LS). Many factors affect the quality of LS, such as temperature. The objective of this study is to find out whether the temperature of the pyrolysis process affects to the total phenol content (TPC), total acid content (TAC), and pH of the LS from SCG. The method of this study was using experiments. The treatments used in LS production are 400°C (T400) and 550°C (T550). To test the TPC, TAC, and pH, this study is using SNI 06-6989.21-2004, SNI 06-2422-1991, and SNI 6989.11-2019. To analyze the difference in the TPC, TAC, and pH due to the temperature, this study uses one-way ANOVA. The average TPC from T400 and T550 is 488 mg/L and 159 mg/L. The average TAC from T400 and T550 is 2.04% and 2.88%. The pH from T400 and T550 are 4.095 and 3.56. The ANOVA towards the TPC, TAC, and pH shows that the P-value of each key parameter is less than the alpha (0.05). This study concludes that temperature affects the TPC, TAC, and pH of the LS.